Research advances of vasohibin family regulating angiogenesis in kidney diseases - Xiong Yan; Xu Chuan-wen; Xu Yan-mei (Linchuang shenzangbing zazhi)
Vascular endothelial injury of renal microvessels and a decrease of peritubular capillaries are vital in the pathogenesis of acute and chronic renal disease.Capable of endodermal regulation of angiogenesis，vasohibin family （VASH） plays an important role in such diseases as acute kidney injury，chronic kidney disease，diabetic nephropathy and renal tumor.Many studies have suggested that VASH is expected to be a molecular marker for diagnosing and treating kidney diseases and it will become an effective protein factor for molecular targeted therapy.This review summarized structural characteristics，biological activities and related studies of vasohibin family members in kidney diseases.